(untitled) (CIPEEX, 2025)
Introduction: Pre-hospital care services in Brazil were created to deal with the high demand for care in traumatic emergencies. Traumatic causes are the second leading cause of pre-hospital care, involving a variety of injuries that vary in severity and type of accident. Thus, the objective of this study was to characterize the clinical and epidemiological profile of incidents related to external causes in the SAMU (Mobile Emergency Care Service) of Anápolis, Goiás. Methodology: This descriptive, retrospective epidemiological study was conducted in Anápolis, Goiás, analyzing SAMU-192 incident reports from January to March 2023. It included all calls during this period, with data collected at the SAMU headquarters and analyzed statistically, after ethical approval and authorization for data use. Results: A total of 1,097 incidents were analyzed, the majority of which involved males aged between 19 and 45 years, originating on public roads, occurring in the afternoon and on weekends. Regarding the type of care, most were emergency calls, and the main cause of external causes were traffic accidents. Conclusion: These findings highlight the importance of pre-hospital care services and the need to improve the efficiency and triage of emergencies, helping to optimize the response to emergencies and reduce trauma-related mortality.